THE ANTECEDENTS OF COMPLAINT BEHAVIOUR AMONG GENERATION Z: ROLE OF INFORMATION ACCESS, COMPLAINT EXPERIENCE, AND ATTITUDES: THE ANTECEDENTS OF COMPLAINT BEHAVIOUR AMONG GENERATION Z - Simanjuntak, Megawati (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2026)
Objective: This study aims to analyze the influence of information access, complaint experience, and complaint attitudes on complaint behavior. Complaints are a key indicator of consumer dissatisfaction and serve as a crucial element in consumer protection. Design/Method/Approach: A quantitative, cross-sectional research design was utilized, employing an online survey distributed to 250 undergraduate students selected through convenience sampling. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) with AMOS 22.0. Originality/Relevance: The study contributes to the understanding of complaint behavior by integrating multiple influencing factors, including access to information and previous complaint experiences. It highlights the interplay between consumer awareness and their willingness to engage in the complaint process. Main Results/Findings: The study demonstrates significant effects of information access, complaint experience, and complaint attitudes on complaint behavior. Additionally, information access and complaint experience significantly influenced complaint attitudes, reinforcing the importance of knowledge and confidence in consumer decision-making. Theoretical Implications: This study enriches the Consumer Complaint Behavior (CCB) theory by demonstrating that information access, complaint experience, and attitudes toward complaints directly influence consumer complaint behavior. Managerial Contributions: The findings emphasize the necessity of consumer education to enhance awareness and confidence in the complaint process. Businesses should provide adequate consumer education on their products and services, while governments must improve awareness regarding consumer rights and responsibilities.